Triple arched gateway, Jijamata Udyan - Ghosh, Ayan (2023)
Completed in 1868, the triple-arched gateway is the main entrance to Jijamata Udyan. William Tracey designed it in the Neo-Palladian style to resemble a Roman triumphal arch. The narrow width between the arches prevented horse-driven carriages from entering. The pediment over the central arch depicts profile portraits of the Prince and Princess of Wales.